EFFECT OF VARIATION IN THE MEASUREMENT OF SPACE CATEGORIES OF WHEAT FARMS IN SULAYMANIYAH WHEAT ON THE LEVEL OF ECONOMIC EFFICIENCY AND ESTIMATE THE SIZE OF THE EFFICIENCY ACHIEVED OPTIMAL RESOURCES. - & Jbara, Rijib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The wheat crop of the most important strategic food grain crops as it’s source of food for more than (35%) of the world’s population, particularly in third world countries from which Iraq.. This study deals with the subject of measuring the economic efficiency of rain-fed farms wheat in the region in order to identify the most important factors affecting the level of efficiency, in addition to estimating the size of the resources generated economic efficiency overall. It was obtained preliminary data from field sources by relying on a stratified random sample of wheat farmers included (225) farm productive season (2013-2014) in the province of Sulaymaniyah. It has been measuring the Total economical efficiency in accordance to the cost function parameters . It was found that the average of the price efficiency for each of the five categories was 74%, 60%, 58%, 63%, and 68% respectively giving a general average of 64%. In addition to that the measured economical efficiency of the five categories of the wheat cultivated farms 60%, 42%, 35%, 30%, and 47% respectively with an average of 44%. The size of the resources achieving the economical efficiency has been calculated and when subjected to comparison, it appears that there is a surplus in all the resources used.